La referencia al Timeo en Física IV 2 - Casnati, María Gabriela (Pontificia Universidad Católica del Perú. Fondo Editorial, 2013)
In this paper, we discuss some possible readings of Physics IV 2, where Aristotle identifies the Platonic χώρα of the Timaeus with ὕλη, μεταληπτικόν and μεθεκτικόν. We will study common features that bring the receptacle of the Timaeus closer to Aristotelian matter and space, and that make it natural for Aristotle to identify χώρα with matter. However, we will try to show that, in spite of the similarities between the receptacle and what Aristotle understands for place and matter, the mechanics of appropriation of the Platonic text that the Stagirite operates, forcing an equivalence with his own technical terms, possibly implies a distortion that, in the end, does not do justice to the formulations of the teacher.

En el presente trabajo, discutiremos algunas lecturas posibles de Física IV 2, donde Aristóteles identifica la χώρα platónica del Timeo con ὕλη, μεταληπτικόν y μεθεκτικόν. Estudiaremos rasgos comunes que acercan el receptáculo del Timeo con la materia y el espacio aristotélicos, y que hacen que Aristóteles encuentre natural identificar la χώρα con la materia. Sin embargo, intentaremos mostrar que, a pesar de las semejanzas entre el receptáculo y lo que Aristóteles entiende por lugar y materia, la mecánica de apropiación del texto platónico que opera el Estagirita, forzando una equivalencia con sus propios términos técnicos, posiblemente implique una distorsión que no termina de hacer justicia a las formulaciones del maestro.
The reference to Timaeus in Physics IV 2
Keywords: Física; Timeo; χώρα; ὕλη; μεθεκτικόν; https://purl.org/pe-repo/ocde/ford#6.03.01